Maya Codex Book Production and the Politics of Expertise: Archaeology of a Classic Period Household at Xultun, Guatemala. Issue 1 (5th January 2015) - Rossi, Franco D.; Saturno, William A.; Hurst, Heather
ABSTRACT The discovery of mural paintings at the Classic Maya site of Xultun, Guatemala, provides an important context for the study of ancient literacy and writing in practice. The mural chamber was a place of writing where the hands of multiple scribes recorded events and astronomical tabulations on walls that were also painted with portraits of ritual specialists and the reigning king. We present evidence suggesting that creation and inscription of indigenous Maya books, called codices, also took place onsite by a specific cohort of ritual specialists called taaj. In this article, we seek to archaeologically "situate" these codex‐like inscriptions in the mural room—revealing a crucial and distinctly Precolumbian window (as opposed to colonial Spanish view) into Maya bookmaking, its practitioners, and the physical contexts in which it was carried out. Together, the images, texts, and archaeological materials found in and around the chamber enable us to contextualize acts of writing and their authorship as well as engage larger questions regarding the social and political structures shaping literacy in Maya society during the eighth century.